Humanizing Islamic Legal Discourse in the Digital Public Space: A Maqāṣid Perspective of Buya Yahya’s Fatwas on LGBT - Mukhammad Nur Hadi (Zamzami Scholar Publishing, 2026)
Digital platforms have become pivotal in shaping religious legal discourse. This study examines the construction of legal humanism in the digital fatwas of Buya Yahya regarding LGBT issues on YouTube. Analyzing fourteen videos from Al-Bahjah TV, the research employs a maqāṣid al-sharī‘ah framework, specifically focusing on ḥifz al-nafs (protection of life). The analysis reveals that while Buya Yahya views LGBT as a curable illness, he vehemently rejects social exclusion. Instead, he advocates for a compassionate approach, emphasizing healing, family preservation, and inclusive embracement over condemnation. This stance prioritizes humanity, acting as a counter-narrative to rigid conservative religious views often found online. This study concludes that Buya Yahya effectively utilizes digital media to mainstream legal humanism, transforming public perception by presenting an Islamic jurisprudence that safeguards human dignity. These findings highlight the potential of digital fatwas in fostering a more humane and moderate religious atmosphere in Indonesia.